Subtitling for the deaf and the hard-of-hearing (SDH): A reception study with Southeastern Brazilian deaf - Araújo, Vera Lúcia Santiago; Vieira, Patrícia Araújo; Monteiro, Silvia Malena Modesto (TradTerm, 2013)
This paper aims at presenting the results of an exploratory research on the reception of subtitled films carried out by group LEAD (Subtitling and Audiodescription) from UECE (State University of Ceara) with deaf individuals from the Southeast region of Brazil. This research is part of a bigger one called MOLES Project (Model of Subtitling for the Deaf) developed from 2009 to 2012 with deaf people from different regions of Brazil, and using subtitled short films made by filmmakers from the state of Ceara. The results suggest that segmentation (having visual, rhetorical and linguistic aspects as criteria) would be more relevant for an efficient reception than subtitle rate. Thus, we intend to open space for new discussions and also glimpse new perspectives in research related to SDH (Subtitling for the Deaf and Hard-of-hearing).